Characteristics and its formation reason analysis of adiabatic shear band produced by gear fracture. (October 2020) - Zhiwei, Zhang; Fan, Wang; Sufen, Liu; Yang, Zhang
Abstract: The formation and characteristics of adiabatic shear band during the fracture of gear assembly were studied. It shows that in the fracture process, the strain required by the adiabatic shear band can be achieved near the failure position of the gear, and thus the adiabatic shear band is generated. The distribution of the adiabatic shear band is discontinuous, and the angle with the gear is about 20 ° to 45 °. With the appearance of adiabatic shear band, a high strain rate is produced, and a lot of heat is produced in some areas. And because of the extremely fast speed, these heat can not be transferred in time, resulting in deformation, which leads to the fracture of gear assembly. At the same time, the critical strain and critical temperature are calculated.